(untitled) (The Review of Diabetic Studies, 2024)
Background: Sugar-sweetened beverage (SSB) consumption is highly prevalent among adolescents and represents a modifiable risk factor for adverse oral health outcomes. Evidence from Saudi Arabia remains limited, particularly regarding the cumulative impact of consumption patterns and preventive interventions. Objective: This study assessed patterns of sugary drink consumption among Saudi adolescents and examined their association with oral hygiene behaviors and clinical oral health outcomes. Methods: A cross-sectional study was conducted among 300 adolescents aged 12–18 years recruited from urban and semi-urban areas. Data on demographic characteristics, SSB consumption, oral hygiene behaviors, and exposure to preventive interventions were collected using structured questionnaires. Clinical oral examinations assessed dental caries using the decayed, missing, and filled teeth (DMFT) index and dental erosion using the Basic Erosive Wear Examination (BEWE). Bivariate correlations and multivariable linear regression analyses were performed. Results: Regular SSB consumption was reported by 95% of participants, with 60% consuming sugary drinks daily and 20% multiple times daily. Carbonated soft drinks were the most frequently consumed beverages (78%). Mean DMFT was 4.8 ± 2.3, and dental erosion was observed in 42% of adolescents. Higher frequency and longer duration of SSB consumption were significantly associated with increased DMFT and BEWE scores (p < 0.01). Daily SSB intake independently predicted higher caries experience (β = 1.87, p < 0.001) and greater dental erosion (β = 0.72, p < 0.01). Participation in preventive programs was associated with marginally improved outcomes, although differences were not statistically significant. Conclusion: Sugary drink consumption is widespread among Saudi adolescents and is strongly associated with increased dental caries and erosion. Despite moderate awareness of oral health risks, preventive behaviors and intervention effectiveness remain limited. Strengthened, multi-level public health strategies are needed to reduce SSB intake and improve adolescent oral health outcomes.